PEER EDUCATOR AS A METHOD TO INCREASE THE BEHAVIOUR OF HIV/AIDS PREVENTION AMONG STUDENTS OF SMK KESEHATAN IN SAMARINDA CITY - Yuliani winarti (Jurnal Ilmu Kesehatan, 2019)
Increasing cases of HIV/AIDS among adolescents in the age of range 15-24 years is getting 25%. Comprehensive knowledge of HIV/AIDS prevention has not helped propel the rising of these cases. Therefore, adolescents need health education related to prevent HIV/AIDS transmission. This study was to analyze the effect of the peer educator method on the prevention of HIV/ AIDS transmission in SMK Kesehatan Samarinda City. The study was a quasi-experiment with a non-equivalent control group with pre-test post-test design. The selection of research subjects was based on purposive sampling technique, beginning with the number of peer educator recruitment as many as 6 people, and each peer educator selected a maximum of 5 peer groups so that 30 case groups were treated with peer educator methods and control of 30 students who received HIV/AIDS prevention modules. Data collection is done using a questionnaire. To see the difference in the average HIV / AIDS prevention measures using the Wilcoxon test with a significance level of p = 0.05. The results showed a statistically significant difference p <0.05 in both groups before and after treatment. The mean changes in prevention measures for HIV / AIDS transmission were higher in the group that received the peer educator method compared to the control group that received the module. The conclusion of this study is that the peer educator method is more effective in increasing prevention measures for HIV / AIDS transmission in Health Vocational students in Samarinda City.